2011
DOI: 10.3109/00048674.2010.522555
|View full text |Cite
|
Sign up to set email alerts
|

Examining Welfare Receipt and Mental Disorders After a Decade of Reform and Prosperity: Analysis of the 2007 National Survey of Mental Health and Wellbeing

Abstract: Income support recipients are much more likely to experience mental disorders than those not receiving payments and there has been little change in the strength of the association between income support receipt and mental disorders over the past decade. Mental disorders represent a substantial barrier to work, community engagement and social participation. A greater focus on mental health in the design and delivery of social policy and services may be an appropriate strategy to promote more positive outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…While VET students with low incomes, like their non-student peers, had a greater risk of high distress, there was no significant association between low income and psychological distress in university students. The results for VET students and non-students are consistent with the substantial evidence that relatively low income, an indicator of low socio-economic status, is associated with mental disorders in the wider community (Butterworth et al, 2011;Fryers et al, 2003;Muntaner et al, 2004). However, given the significant association of psychological distress with financial problems, it is somewhat surprising that low personal income was not also associated with psychological distress in university students.…”
Section: Discussionsupporting
confidence: 86%
“…While VET students with low incomes, like their non-student peers, had a greater risk of high distress, there was no significant association between low income and psychological distress in university students. The results for VET students and non-students are consistent with the substantial evidence that relatively low income, an indicator of low socio-economic status, is associated with mental disorders in the wider community (Butterworth et al, 2011;Fryers et al, 2003;Muntaner et al, 2004). However, given the significant association of psychological distress with financial problems, it is somewhat surprising that low personal income was not also associated with psychological distress in university students.…”
Section: Discussionsupporting
confidence: 86%
“…Despite calls for greater focus on mental illnesses in policy design [29][30][31] , our results demonstrate that there is limited evidence relating to policy design for disability income support and mental illnesses in Australia and Ontario. The evidence that is available overwhelmingly suggests that disability income support, especially the assessment process, is not adequately designed for mental illnesses.…”
Section: Discussionmentioning
confidence: 56%
“…While they did find significant increases in the rates of mental health problems amongst partnered parents the authors concluded this was due to changes in the data collection methodology rather than true changes in the population (Butterworth et al 2011).…”
Section: Impact On Mental and Physical Healthmentioning
confidence: 83%